Investigation of wood properties and resistance of 25-year-old Gmelina arborea wood selected from crown region to termite attack - Samuel Oluyinka Olaniran; Ebenezer Iyiola; Abdulmuhmeen Abbey Oyekola (Maderas: Ciencia y Tecnología, 2023)
Gmelina arborea is widely planted and produces many useful products. However, the upper portion of the stem might be useful for some practical applications if properly managed and harvested. In order to explore the potential of this residues, this study investigated the physical, mechanical properties, and resistance of 25-year-old Gmelina arborea (gamhar) wood from the crown region to termite attack. This is with a view to enhance the use of harvesting residues of Gmelina arborea (gamhar) such that the wood in the crown region is used as the main trunk in various applications. The following wood properties including density, modulus of elasticity, modulus of rupture, and compression strength were investigated on crown wood of 25-year-old Gmelina arborea (gamhar). This study compared with results obtained from previous studies for the bole. Test for the natural resistance of the crown wood was carried out at the timber graveyard where the samples were exposed to termites for 10 weeks to determine the weight loss. The wood samples were rated weekly according to the America Standard of Testing Material. Our results showed that there were significant differences in the density of the crown wood of the three selected 25-year-old Gmelina arborea (gamhar) stands. The results for the mechanical properties of the crown wood of the three selected 25-year-old Gmelina arborea (gamhar) trees showed that there were significant differences in the compression and modulus of rupture of the wood samples from the crown region while there was no significant difference in the modulus of elasticity among the selected stands. Visual rating results showed that termite attack ranged from moderate to heavy attack, while the weight loss was not significantly different among the sampled trees. This study has shown that the density and mechanical properties of the crown wood are comparable to those from the trunk. Hence, the crown wood can be used in application as the stem wood. Also, the study has shown that wood from crown region of Gmelina arborea (gamhar) are prone to termite attack and non-durable as the wood obtained from the stem. Therefore, there is a need to apply treatments that can improve its durability and enhance its service life.